Native T1-mapping detects the location, extent and patterns of acute myocarditis without the need for gadolinium contrast agents - Ferreira, V; Piechnik, S; Dall'Armellina, E; Karamitsos, T; Francis, J; Ntusi, N; Holloway, C; Choudhury, R; Kardos, A; Robson, MD; Friedrich, MG; Neubauer, S (BioMed Central, 2014)
Background: Acute myocarditis can be diagnosed on cardiovascular magnetic resonance (CMR) using multiple techniques, including late gadolinium enhancement (LGE) imaging, which requires contrast administration. Native T1-mapping is significantly more sensitive than LGE and conventional T2-weighted (T2W) imaging in detecting myocarditis. The aims of this study were to demonstrate how to display the non-ischemic patterns of injury and to quantify myocardial involvement in acute myocarditis without the need for contrast agents, using topographic T1-maps and incremental T1 thresholds. Methods. We studied 60 patients with suspected acute myocarditis (median 3 days from presentation) and 50 controls using CMR (1.5 T), including: (1) dark-blood T2W imaging; >(2) native T1-mapping (ShMOLLI); (3) LGE. Analysis included: (1) global myocardial T2 signal intensity (SI) ratio compared to skeletal muscle; (2) myocardial T1 times; (3) areas of injury by T2W, T1-mapping and LGE. Results: Compared to controls, patients had more edema (global myocardial T2 SI ratio 1.71 ± 0.27 vs.1.56 ± 0.15), higher mean myocardial T1 (1011 ± 64 ms vs. 946 ± 23 ms) and more areas of injury as detected by T2W (median 5% vs. 0%), T1 (median 32% vs. 0.7%) and LGE (median 11% vs. 0%); all p < 0.001. A threshold of T1 > 990 ms (sensitivity 90%, specificity 88%) detected significantly larger areas of involvement than T2W and LGE imaging in patients, and additional areas of injury when T2W and LGE were negative. T1-mapping significantly improved the diagnostic confidence in an additional 30% of cases when at least one of the conventional methods (T2W, LGE) failed to identify any areas of abnormality. Using incremental thresholds, T1-mapping can display the non-ischemic patterns of injury typical of myocarditis. Conclusion: Native T1-mapping can display the typical non-ischemic patterns in acute myocarditis, similar to LGE imaging but without the need for contrast agents. In addition, T1-mapping offers significant incremental diagnostic value, detecting additional areas of myocardial involvement beyond T2W and LGE imaging and identified extra cases when these conventional methods failed to identify abnormalities. In the future, it may be possible to perform gadolinium-free CMR using cine and T1-mapping for tissue characterization and may be particularly useful for patients in whom gadolinium contrast is contraindicated. © 2014 Ferreira et al.; licensee BioMed Central Ltd.